2021
DOI: 10.1088/1755-1315/869/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Conservation impact from Lamteungoh fishing village: lesson learned from Aceh coastal area

Abstract: Indonesia is an archipelago nation with most of its big cities lays on or adjacent to the coastal area. Thus, driving huge demand for marine and fisheries resources in the concerning region. However, with a long coastline, the rural areas or coastal villages are distributed along the coast surrounding the archipelago, therefore it is reasonable to consider the impact being given by the coastal village on its effort toward conservation. In this study, we applied the Rapid Appraisal of Fisheries Management Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Following the study results, direct involvement by the community has a significant impact on preserving the environment around them [24]- [26]. Involvement is a fundamental activity in achieving the changes desired by the community in their environment [27]. On the other hand, several studies have revealed that variables such as knowledge also contribute to waste management in the community.…”
Section: Figure 1 Structural Modelmentioning
confidence: 82%
“…Following the study results, direct involvement by the community has a significant impact on preserving the environment around them [24]- [26]. Involvement is a fundamental activity in achieving the changes desired by the community in their environment [27]. On the other hand, several studies have revealed that variables such as knowledge also contribute to waste management in the community.…”
Section: Figure 1 Structural Modelmentioning
confidence: 82%
“…The impact of extreme maritime events, such as hurricanes, earthquakes, and tsunamis, on fishery resources is noteworthy. These events have resulted in considerable alterations to both the biological and physical attributes of fishery resources in a swift and substantial manner [33]. According to research conducted in Depok Village, there has been a noticeable decrease in fish catches.…”
Section: The Impact Of Climate Change On the Agromaritime Sectormentioning
confidence: 99%
“…This situation is further compounded by the presence of IAB and OAB in coastal waters, which pose a higher risk of marine plastic contamination than OAB in the central and offshore areas [50]. Human activity, also known as anthropogenic activity [33]. Yamamoto's research in 2023 revealed that protecting natural resources is a more efficient choice than pursuing other land uses such as fish farming and palm oil plantations.…”
Section: Environmental Issues Governance and Conservationmentioning
confidence: 99%